Impact of Diabetes Mellitus on Atrial Fibrillation Recurrence and Major Adverse Cardiac and Cerebrovascular Events following Catheter Ablation - Mingjie Lin; Juntao Wang; Bing Rong; Kai Zhang; Tongshuai Chen; Wenqiang Han; Tong Hu; Tianyu Wang; Haonan Deng; Jingquan Zhong; Lin Wu (International Journal of Clinical Practice)
Introduction. Further evidence is required to understand the impact of preexisting and newly diagnosed diabetes mellitus (DM) on atrial fibrillation (AF) recurrence and major adverse cardiac and cerebrovascular events (MACCEs) following catheter ablation. Materials and Methods. Data from 1,685 patients (1,406 without DM vs. 279 with DM) who underwent AF catheter ablation between 2015 and 2019 were analyzed. These participants were prospectively monitored for incidents of AF recurrence and MACCE over an average period of 58.1 months. Results. A higher incidence of AF recurrence (24.6% vs. 34.4%) and a greater frequency of MACCE (6.5% vs. 9.3%) were observed among DM patients. Kaplan–Meier curves indicated that DM significantly increased the rates of AF recurrence, with a hazard ratio (HR) of 1.506 and a 95% confidence interval (CI) of 1.165–1.948 (p=0.0003). This association persisted in the propensity-matched cohort. DM was independently predictive of AF recurrence after adjusting for potential risks using Cox regression analysis. Notably, new-onset DM was also found to be an independent predictor of AF recurrence. Similarly, DM was an independent risk of MACCE (HR [95% CI], 2.273 [1.120–4.615], p=0.023). Conclusions. Both existing DM and newly diagnosed DM were identified as independent risk factors for AF recurrence following ablation; they also significantly impacted MACCE outcomes. This study underscores the urgent need for careful management of DM among individuals undergoing AF ablation in order to reduce the likelihood of arrhythmic relapse. This analysis utilized data from a prospective observational study registered in the Chinese Clinical Trial Registry on July 20, 2014 (ChiCTR-OCH-14004674).